2016
DOI: 10.1007/s10750-016-2982-5
|View full text |Cite
|
Sign up to set email alerts
|

Partial diel vertical migration in an omnivorous macroinvertebrate, Mysis diluviana

Abstract: Partial migration, whereby only a portion of a population migrates, has just recently received attention in aquatic systems. Partial diel vertical migration (DVM) has received even less attention but could significantly influence our understanding of trophic interactions and nutrient movement in open water systems. Recent work in the Baltic Sea shows differences in isotope composition between benthic and pelagic Mysis salemaai sampled at night, suggesting that partial DVM may be fixed at the individual level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…A nonmigrating benthic portion of Mysis that remains on or near the bottom of deep lakes, and thus unavailable to pelagic gear at night when Mysis populations are sampled, could present complications for sampling programs and mass‐balance food web models, especially if the nonmigrants represent a large proportion of the population biomass or a disproportionate fraction of particular life‐stages (e.g., adult females; Euclide et al ; O'Malley et al ). Our results confirm the presence of Mysis in close contact with the sediment surface throughout the night each month from spring to autumn, confirming that Mysis partial DVM is common in Lake Champlain (Euclide et al ; O'Malley et al ). Our results also suggest that Mysis densities may be much higher on benthic habitats than previously estimated using benthic sleds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A nonmigrating benthic portion of Mysis that remains on or near the bottom of deep lakes, and thus unavailable to pelagic gear at night when Mysis populations are sampled, could present complications for sampling programs and mass‐balance food web models, especially if the nonmigrants represent a large proportion of the population biomass or a disproportionate fraction of particular life‐stages (e.g., adult females; Euclide et al ; O'Malley et al ). Our results confirm the presence of Mysis in close contact with the sediment surface throughout the night each month from spring to autumn, confirming that Mysis partial DVM is common in Lake Champlain (Euclide et al ; O'Malley et al ). Our results also suggest that Mysis densities may be much higher on benthic habitats than previously estimated using benthic sleds.…”
Section: Discussionmentioning
confidence: 99%
“…Partial migration is a result of individual variability in migratory behavior, where not all individuals in a population migrate (Chapman et al ). Partial DVM has been the term used to describe invertebrates that demonstrate variability in their DVM behavior within a population (Frost and Bollens ; Euclide et al ). Consequently, population estimates of meroplanktonic species that exhibit partial DVM need to account for both migrant and nonmigrant individuals.…”
Section: Qualitative Tradeoffs With Various Sampling Methods Used To mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand mysid migration, we need to consider external and internal conditions (Nathan et al, 2008) unclear. Several early studies proposed such alternative behaviours (Morgan, 1980;Rybock, 1978), and more recent studies using stable isotopes and genetics have found suggestive but mixed results (Euclide et al, 2017;Ogonowski et al, 2013). Another possibility is the presence of personality traits that influence, or at least reflect, differences in movement, including migration (Chapman et al, 2011;Mettke-Hofmann, Ebert, Schmidt, Steiger, & Stieb, 2005;Nilsson, Nilsson, Alerstam, & Backman, 2010;Sih & Watters, 2005 Sommer et al, 2012) and benthic resources, and observations from Lake Ontario (Johannsson et al, 2001).…”
Section: (1) What Body-states and Environmental Conditions Determinmentioning
confidence: 99%
“…Recent studies, however, indicate that Mysis exhibit partial DVM, whereby a portion of the population does not ascend but remains on bottom at night (Euclide, Hansson, & Stockwell, 2017;Ogonowski, Duberg, Hansson, & Gorokhova, 2013;O'Malley, Dillon, Paddock, Hansson, & Stockwell, 2018;.…”
Section: Introductionmentioning
confidence: 99%